Feasibility and acceptance of self-hypnosis to reduce chronic stress levels on family in-home caregivers of elderly people: protocol for the POSSAID pilot, randomised, wait-list controlled trial - Léa Bruneau; Danielle Reynaud (BMJ Open)
Introduction Family members who care for elderly people experience high levels of chronic stress because of the intensive assistance they provide permanently to those who are losing their autonomy. Often considered a burden, this stress causes serious consequences to their health and worsens their quality of life (QoL). Reducing caregivers’ chronic stress via self-hypnosis protocols may be an effective treatment. The objective is to evaluate the feasibility and acceptance of self-hypnosis protocols taught by hypnotherapy-trained nurses to reduce the chronic stress of in-family caregivers.Methods and analysis This study is a prospective, monocentric, non-blinded, parallel, pilot, randomised waitlist-controlled trial that will be conducted at the University Hospital of Reunion Island. Sixty participants will be randomly allocated to one of two groups: a self-hypnosis group (intervention) or a waitlist control group. After an 8-week training programme, intervention participants will practice self-hypnosis for ten minutes/day over 8 weeks and subsequently be followed up for 16 weeks thereafter. The primary outcome is to assess the feasibility of a 16-week self-hypnosis protocol for in-family caregivers. Secondary outcomes include the evaluation of the effects of practising self-hypnosis among in-family caregivers of elderly people concerning their stress levels, sleep disorders, levels of fatigue, and QoL at 2, 4 and 8 months on an exploratory basis.Ethics and dissemination Ethics approval was obtained from the Institutional Ethics Committee CPP Ile de France VI—Groupe Hospitalier Pitié Salpêtrière on 14 April 2021 (ID RCB: 2021-A00009-32). All participants will receive information about the trial in verbal and written forms. They will give an oral consent which is notified in a dedicated research file prior before enrolment. Results will be published in peer-reviewed journals as well as presented and disseminated at conferences.Trial registration number NCT04909970.